Why do parents refuse childhood vaccination? Reasons reported in Finland - Nurmi Johanna; Harman Bronwyn (SAGE PUBLICATIONS LTD, 2025)
Aims:
This article examines the reasons for partial and complete refusal of childhood vaccination as reported by parents in Finland. It analyzes perceptions and experiences central in vaccination decisions.
Methods:
The analysis is based on 38 in-depth interviews with Finnish parents who have refused all or several vaccines for their children. The interviews were analyzed using qualitative content analysis.
Results:
Three categories of reasons were identified in the analysis: 1) risks and effects of vaccination - concern about and/or experiences of possible side-effects was the most important reason for avoiding vaccines; 2) distrust - participants did not trust vaccination recommendations made by health officials and medical professionals due to perceived bias in medical research, ties between health officials and the pharmaceutical industry, and personal experiences of (suspected) adverse effects and the way these concerns were received in healthcare institutions; 3) health perceptions and practices - parents supported their vaccination choices with complementary and alternative medicine treatments and alternative health understandings. Many stated that contracting vaccine-preventable illnesses would provide longer lasting and more 'natural' immunity than vaccination, and possibly other health benefits.
Conclusions:
A loss of trust in medical and public health actors was central to the process in which parents came to question, contest, and eventually refuse childhood vaccination. The adverse effects of the Pandemrix vaccine in 2009-2010 have been important in leading to distrust and contestation. Distrust may relate to personal experiences of (suspected) adverse effects or to broader concerns over the neutrality of health authorities and the trustworthiness of medical research.